Gendered domestic violence and abuse in popular culture - Ramon, Shulamit; Lloyd, Michele; Penhale, Bridget (Emerald studies in popular culture and gender, 2020)
As binge-watching and streaming lead to increasing amounts of content and screen time, understanding how domestic violence and abuse is portrayed in popular culture and its impact on DVA in our society is more important than ever. This collection demonstrates how networked communication is influencing activism, both online and in the real-world.